Does Information Sharing Reduce the Role of Collateral as a Screening Device? - Artashes Karapetyan; Bogdan Stacescu (Norges Bank, 2012)
Information sharing and collateral reduce adverse selection costs, but are costly for lenders. When a bank learns more about the types of its rival's borrowers through information sharing (e.g., credit bureaus), it might seem that this information should substitute the role of collateral in screening their types. We instead show that information sharing may increase, rather than decrease, the role of collateral, which can be required in loans to high-risk borrowers in cases when it is not in the absence of information sharing. We extend to show that ex ante screening can substitute both collateral and information sharing.
hdl:11250/2496820
Keywords: G21; L13; 330; bank competition; information sharing; collateral